‘The Dung-heap and the Flower’: Gissing’s Nether World - Nigel Messenger (Cahiers Victoriens et Edouardiens)
This paper examines the creative dynamic behind Gissing’s most successful slum novel, The Nether World, by speculating on Gissing’s own ‘nether world’: in particular, his social disgrace following his conviction for petty theft at Owens College, Manchester and his sexual preference for uneducated, working class girls. Using the concept of ‘abjection’ as theorised by Julia Kristeva in Powers of Horror, the paper goes on to discuss some of the language, social settings and characters of The Nether World, and concludes by suggesting that Gissing’s novel anticipates some aspects of twentieth-century Modernism.